Classification, Valuation and Real Options Analysis of Climate Change Projects in Africa: A case study of Ghana in West Africa - Asumadagwine, Godwin (Department of Mathematics and Applied Mathematics, 2023)
Projects and investments such as those of R & D and climate change are subject to several uncertainties. These uncertainties, if not properly managed, could defeat the actual purpose and target of the project. In this work, we identify flexibility as a way in which uncertainties can be managed. As the main aim of investments is to make profit, it is significant that investors conduct an in depth study of the project under consideration. This will aid in cost-benefit analysis to ascertain whether it is financially worth it or not. Real options in finance, is the tool that has proved effective in that regard. However, not every project can be analysed using real options. This thesis introduces real options in climate change investment in Africa (Ghana), 2014-2020. To determine whether real options could be applied, we introduce and estimate certain measures: flexibility, optionability and realizability. These metrics help us to identify the project in which real options can be used. In this case, we characterize real options into mechanisms and types. The mechanisms are noted to be the enablers of real options while the types are the particular ones enabled. This work also introduces the Decision Structure Matrix (DSM) in climate change investment. The logical Coupled Dependency Matrix (C-DSM) is used to specify the logical relations that exist among dependencies in the project. The logical dependencies are then used for the estimation of the metrics . This study serves as the basis for the application of real options analysis in climate change investments.